Family papers, 1825-82 - Burruss, John C. (Plantation records, 1973)
Methodist minister of Virginia and planter of Woodville and Cliffwood Plantation, Pickneyville, Miss. Correspondence and personal and business papers of Burruss, his son, John William F. Burruss, his daughter, Mary (Burruss) McGehee, and Edward McGehee Burruss and Ann (Burruss) Kennard, children of John William F. Burruss. Includes papers of the family of McGehee, of Wilkinson Co., Miss. The papers relate to the Methodist church, especially in Mississippi, the social and intellectual life of wealthy planter families, student life at southern and eastern colleges, military and civilian life during the Civil War, and religious justification of slavery.